Does Climate Change Transfer Poverty from Rural to Urban Areas? Implications for Regional Sub-Saharan Research Agenda - Thanyani Madzivhandila; Aklilu Asha (African Human Mobility Review, 2024)
There is growing recognition that climate change is a worldwide phenomenon with far-reaching effects and that it is linked to an increase in the frequency of extreme weather occurrences. In rural areas of most of the sub-Saharan countries and other developing countries in the world, the frequent occurrences of extreme weather events such as flooding, heat waves, and drought have significantly destroyed livelihood activities of poor communities. Unfavorable geographic characteristics, a lack of resources, and a higher reliance on climate-sensitive sources of income among many community members in poor nations all contribute to the impact. These include livelihood activities associated with land use and agricultural practices. Sadly, the population’s capacity and incentive to stay in rural areas have been altered because of climate change and its detrimental impacts on agricultural output, income, and subsistence living; as a result, many rural dwellers are migrating to urban areas. Rural populations migrate to urban areas in search of economic opportunities to earn a living. It is evident that the expected opportunities in urban areas are not always available; thus, most of the rural migrants are stuck in informal settlements, shanty towns, and slums without access to services. Consequently, it is evident that climate change is somehow transferring poverty from rural to urban areas. This study adopted the push/pull theory as a theoretical framework to guide the discussion and analysis. Based on an extensive review of the existing literature using qualitative document analysis, the purpose of this article is to examine the role of climate change on rural–urban migration, which ultimately contributes to the increase in urban poverty. The article concludes by reviewing the current (limited) research on climate change and poverty and argues for a research agenda in the context of sub-Saharan Africa toward sustainable ways to respond to the challenges of climate-induced migration, urbanization, and poverty.